UNTRAINED BUT UNDETERRED: CHALLENGES AND STRATEGIES OF RECEIVING TEACHERS IN INCLUSIVE EDUCATION (Proceedings of International Conference on Special Education, 2025)
Inclusive education seeks to integrate learners with special educational needs (LSENs) into mainstream classrooms, yet many receiving teachers lack formal training in special education, creating challenges in curriculum adaptation, assessment, and behavioral management. This study examines the experiences, strategies, and support needs of receiving teachers who educate learners with special needs without specialized training. Using a qualitative phenomenological approach, data were collected through focus group discussions and individual interviews with receiving teachers from various schools in Davao Region, Philippines. Findings reveal significant difficulties in modifying curricula to meet diverse learner needs, uncertainty in implementing fair assessment methods, and struggles with managing LSEN behaviors, which contribute to teacher stress and feelings of inadequacy. Despite these challenges, teachers demonstrate resilience by employing self-directed learning, Universal Design for Learning (UDL), and peer collaboration. However, inequitable resource distribution and a lack of structured professional development hinder the effective implementation of inclusive practices. Teachers emphasized the urgent need for targeted training programs, structured mentoring, and institutional support to enhance their instructional effectiveness. The study concludes that equipping receiving teachers with specialized training and adequate resources is critical to strengthening inclusive education. It highlights the necessity for education policymakers to develop comprehensive training and support systems to address the pressing needs of receiving teachers. By bridging these gaps, schools can create a more inclusive learning environment, ensuring that learners with special needs receive appropriate support to thrive academically and socially. These findings contribute to the ongoing discourse on inclusive education and provide insights into enhancing teacher preparedness and institutional support.